(untitled) (Journal of Advanced Research in Social Sciences, 2019)
Economic crime, social abuse, dilapidation of public funds, vices, perverse behavior, deviant behavior, etc., are among the qualifiers borrowed from criminology and economic psychopathology to describe the phenomenon of corruption. Corruption, because of its extent and its multidimensional form, has become a global phenomenon. The degree of corruption is now the barometer of the political and economic health of a country. The effects of corruption on the economy, on development and on society are disastrous and seriously threaten the stability of the social system. Beyond its economic aspect, corruption touches practically all spheres of social life. Consequently, like economics, other disciplinary fields (economic psychology, sociology, anthropology, legal sciences, etc.) are dedicated to the study of corruption. My article aims to explain the phenomenon of corruption from the point of view of economic psychology, a relatively recent scientific field, since the consequences of corruption are not only economic but also psycho-sociological. Values such as merit, fairness, justice, transparency and honesty are being flouted.